Achieving Social Change: A Matter of All for One?. (September 2015) - de Lemus, Soledad; Stroebe, Katherine; Stroebe, Katherine; de Lemus, Soledad
<x xml:space="preserve">Abstract</x> Recently, there has been a growing interest in not only understanding the processes underlying responses to disadvantage, and ways of reducing prejudice, but also to gain insight into how experiences of prejudice and social disadvantage affect the need to address one's disadvantage. Our goal in this issue is to discuss how and when low status group members move from experiences of individual versus collective disadvantage to social change. In this article, we consider the individual coping and social change literature, departing from the analyses of individual‐level responses to disadvantage, to those at the collective level, to discuss how both strands of research relate to social change. Throughout this article, we introduce the contributions to this special issue and discuss the caveats and paradoxes they raise with regard to the existent literature.